Application of the Recitation Method to Improve Students' Critical Thinking Skills in Islamic Religious Education Subjects in Vocational Schools - Hamzah; Wardah Hidayah Saadah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2023)
Recitation method is a method to improve critical thinking skills. From the facts in the field it can be seen that critical thinking skills are still low, especially at Darel Hikmah Vocational School in Pekanbaru City where symptoms of low critical thinking skills are found, namely students are unable to identify conclusions, students are unable to identify irrelevance and relevance, students are unable to find differences, students unable to deceive what is observed. The formulation of the problem in this study is whether the application of the recitation method can improve students' critical thinking skills in Islamic Religious Education subjects at Darel Hikmah Vocational School, Pekanbaru City? So the purpose of this study was to examine the improvement of critical thinking skills by applying the recitation method in class X Multimedia SMK Darel Hikmah Pekanbaru City. By using classroom action research (PTK), and the data has been assigned a test to measure students' critical thinking skills. Data were analyzed using the percentage of student test results using descriptive statistics. The results showed that prior to using the recitation method in the pre-cycle, students' critical thinking skills were classified as very low (37%). After the recitation method was applied to the cycle, students' critical thinking skills increased to (79%) in the sufficient category. Continuing in cycle 2, students' critical thinking skills increased to (90%) with a very high category. So it can be concluded that the application of the recitation method can improve critical thinking skills in Islamic Religious Education subjects at Darel Hikmah Vocational School, Pekanbaru City